1991
DOI: 10.1037/0894-4105.5.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Sparing of cognitive executive functions and impairment of motor functions after industrial exposure to lead: A field study with control group.

Abstract: 41 lead-smelter workers and 37 nonsmelter workers were evaluated for cognitive executive function, motor function, and exposure to lead. Smelter workers had an average blood-lead level more than 6 times the Canadian urban average. Multivariate comparisons of the exposed and unexposed groups on all the measures of executive function revealed no trend toward a toxic effect of lead. Canonical correlation analysis (corrected for age and education) of the exposed group revealed no significant relations between dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…These findings are consistent with previous studies of chronic lead exposure where higher exposures (e.g., years of exposure; integrated blood lead (IBL); bone lead) were associated with poorer performance on motor and visuomotor tasks [Braun and Daigneault, 1991;Bolla et al, 1995;Lindgren et al, 1996;Bleecker et al, 1997;Payton et al, 1998]. However, Hanninen et al [1998] and Bleecker et al [1997] found that history of blood lead was a better predictor of performance than bone lead while Stokes et al [1998] did not find an association between bone lead and neurobehavioral performance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with previous studies of chronic lead exposure where higher exposures (e.g., years of exposure; integrated blood lead (IBL); bone lead) were associated with poorer performance on motor and visuomotor tasks [Braun and Daigneault, 1991;Bolla et al, 1995;Lindgren et al, 1996;Bleecker et al, 1997;Payton et al, 1998]. However, Hanninen et al [1998] and Bleecker et al [1997] found that history of blood lead was a better predictor of performance than bone lead while Stokes et al [1998] did not find an association between bone lead and neurobehavioral performance.…”
Section: Discussionsupporting
confidence: 90%
“…Although the analysis of variance by exposure group did not reveal significant differences for the other tasks of vigilance and visuomotor speed, step-wise regression analyses documented bone lead as a significant predictor of total errors on a speeded task of auditory information processing (PASAT) and visuomotor speed for the non-preferred hand (simple visual reaction time). These findings are consistent with previous studies of chronic lead exposure where higher exposures (e.g., years of exposure; integrated blood lead (IBL); bone lead) were associated with poorer performance on motor and visuomotor tasks [Braun and Daigneault, 1991;Bolla et al, 1995;Lindgren et al, 1996;Bleecker et al, 1997;Payton et al, 1998]. However, Hanninen et al [1998] and Bleecker et al [1997] found that history of blood lead was a better predictor of performance than bone lead while Stokes et al [1998] did not find an association between bone lead and neurobehavioral performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In some cases, the differences in mean values reported by different studies leads one to question whether these studies did, indeed, use the same tests. For example, for simple reaction time (non-preferred hand), Braun and Daigneault, 26 Haenninen et al, 28 and Repko et al 34 reported means for the exposed groups of 178.78, 1310, and 29.62, respectively. The source of such discrepancy is not apparent, although it is possible that different studies used different numbers of items.…”
Section: Discussionmentioning
confidence: 99%